2001
DOI: 10.1210/endo.142.9.8369
|View full text |Cite
|
Sign up to set email alerts
|

S179D-Human PRL, a Pseudophosphorylated Human PRL Analog, Is an Agonist and Not an Antagonist

Abstract: For many years, our group has been involved in the development of human PRL antagonists. In two recent publications, S179D-human PRL, a human PRL analog designed to mimic a putative S179-phosphorylated human PRL, was reported to be a highly potent antagonist of human PRL-induced proliferation and signaling in rat Nb2 cells. We prepared this analog with the aim of testing it in various bioassays involving the homologous, human PRL receptor. In our hands, S179D-human PRL was able to stimulate 1) the proliferatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 59 publications
(118 reference statements)
5
23
0
Order By: Relevance
“…2A). We have shown previously that the hGH analog G120K-hGH is also a potent antagonist in this assay (50), whereas the analog S179D-hPRL is not an antagonist but is instead a super-agonist (42). Similar observations were confirmed in this study (not shown).…”
Section: Cell-based Bioassayssupporting
confidence: 91%
See 3 more Smart Citations
“…2A). We have shown previously that the hGH analog G120K-hGH is also a potent antagonist in this assay (50), whereas the analog S179D-hPRL is not an antagonist but is instead a super-agonist (42). Similar observations were confirmed in this study (not shown).…”
Section: Cell-based Bioassayssupporting
confidence: 91%
“…We believe that removal of the two N-terminal cysteines (Cys 4 -Cys 11 ) prevents formation of covalent multimers involving intermolecular disulfide bonding between these residues. 3 Production of S179D was less efficient, probably because of misfolding as reported previously (42).…”
Section: Production and Characterization Of Hprl Analogs In E Colisupporting
confidence: 59%
See 2 more Smart Citations
“…However, when used alone and at high concentrations in cells that cannot activate alternate splicing of the receptor (see later), it shows some agonist activity, with about a two log increase in the amount required for equivalent activity to the unmodified hormone (Bernichtein et al, 2001;Soares et al, 2006). However, there is no circumstance in vivo when unmodified PRL is absent.…”
Section: S179d Prl Inhibits Cell Proliferationmentioning
confidence: 99%